Effect of processing methods on fatty acid composition and flavour profile of clarified butter (ghee) obtained from Deoni and Holstein Friesian cow breeds - Deepshikha Kataria; Gurmeet Singh (Food Chemistry: X)
The study investigated the impact of three processes—curd-butter (CD), cream-butter (CM) and fermented cream-butter (FC) on fatty acid composition and volatile profiles of clarified butter (ghee) obtained from two cow breeds, Deoni (DN) and Holstein Friesian (HF). Gas chromatography-mass spectrometry (GC–MS) identified 26 fatty acids in ghee. There was no difference in fatty acid composition due to processing. Significant differences were observed by breed, with HF ghee exhibiting higher polyunsaturated fatty acids and α-linolenic acid than DN ghee. Headspace GC–MS detected 57 volatile compounds. Ghee made with CD and FC processes exhibited higher levels of acids, alcohols, heat degradation products, lactones, ketones, 5-hydroxymethylfurfural and maltol in both breeds. These findings suggest that processing methods alter ghee's volatile compounds without significantly affecting fatty acid composition. Since ghee is a complex lipid, untargeted lipidomics and metabolomics studies can provide further insight into the effects of processing on ghee. This study can guide dairy processors in selecting milk sources and ghee processes to enhance flavour in ghee while maintaining fatty acid composition across cow breeds for product improvement.